The ‘most beautiful place’ where ‘it’s not possible to live’: a qualitative study of relational well-being in an area of climate disaster risk, Bangladesh [data] - Lilier, Kyra (Universität, 2025)
Purpose: Climate change is the greatest global health threat of the 21st century, but little is known about well-being in climate vulnerable populations. We investigate how well-being is shaped and influenced in such a population, where unique and common stressors draw on human well-being. Methods: We present findings from 60 semi-structured in-depth interviews from an area of climate disaster risk in Bangladesh. We inductively analyzed our data following a Reflexive Thematic Analysis approach and then deductively applied a Relational Well-being (RWB) framework to organize refined themes around the importance of relationships for well-being as personal, societal, and environmental drivers. Results: We found that well-being was influenced negatively by factors such as financial worries, forced migration, social pressure, and natural disasters. Well-being was influenced positively by factors such as financial satisfaction, voluntary migration, social support, and place attachment. Conclusions: Using relational well-being as a conceptual lens allowed us to explore the dynamism and complexity of influencing factors on well-being that were partly specific to the local context and partly rooted in wider societal and global structures. Policies which aim to improve the well-being of climate vulnerable populations should consider relational well-being as a conceptual tool to leverage locally available informal resources, such as supporting reciprocal relationships with place and people.